Immuno-Impaired Expression of Synaptophysin, GFAP and Nissl Substances in the Cerebral Cortex of Diabetic Wistar Rats; Evaluation of Andrographis Paniculata Effects - Ismail Olasile Onanuga; Royhan Olamide Folarin; Elijah Taiwo Muniru; Ridwan Babatunde Ibrahim; Ibe Michael Usman; Ayoola Isaac Jegede; Onyemaechi Okpara Azu; Temidire Odunayo Obaya; Moses Oluwasegun Kehinde (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Diabetic hyperglycemia is associated with severe complications, including neuropathy and cognitive impairment. This study examines the neuroprotective effects of Andrographis paniculata (AP) on the cerebrum cortex of alloxan-nicotinamide-induced diabetic male Wistar rats. Thirty-five male Wistar rats were randomly divided into five groups (A–E), each with seven rats. Diabetic hyperglycemia was induced via a single intraperitoneal injection of nicotinamide (110 mg/kg) followed by alloxan (120 mg/kg). Treatment included Andrographis paniculata, metformin and a combination of both. Untreated diabetic hyperglycemia resulted in significant cerebral damage, indicated by weight loss, decreased brain weight, and neuronal degradation. Andrographis paniculata treatment provided partial neuroprotection. Metformin demonstrated significant neuroprotective effects by reducing hyperglycemia, preventing weight loss, and preserving neuronal structure. Combination therapy suggested potential synergistic effects, showing improvements in blood glucose, body weight, brain weight, cerebral morphology, and histochemistry. Increased synaptophysin expression and reduced astrocyte activation via GFAP expression were observed with combination therapy. These findings support the therapeutic potential of Andrographis paniculata, alone or combined with metformin, in managing hyperglycemic neuropathies.